Diagnostic Difficulties in Pathological Laboratories in Developing Countries: A Case Report of Differentiated Squamous Cell Carcinoma in a Young Togolese Woman - Tchin Darré; Lantam Sonhaye; Mazamaesso Tchaou; Abdoul-Samadou Aboubakari; Bingo K. M’Bortche; Kofi Amégbor; Gado Napo-Koura (Case Reports in Pathology)
We report a case of poorly differentiated squamous cell carcinoma of the vulva induced by human papillomavirus in a 23-year-old woman, in whom we experienced diagnostic difficulties.